Comparison of physico-chemical quality of different strawberry cultivars at three maturity stages - D. Boonyakiat (2018)
© All Rights Reserved. Comparison of physico-chemical quality of strawberry fruit cv. Praratchatan 60, 72 and 80 at 25, 50 and 75% color break was investigated. Strawberry fruit cv. Praratchatan 60 and 72 had prominent numbers of conic-shaped fruit which were 77.78 and 62.22%, respectively, while moderate numbers were found in strawberry fruit cv. Praratchatan 80 (46.67%). Fruit weights and fruit sizes in terms of width, length and thickness were different among three cultivars. Strawberry fruit characteristics and chemical properties also varied among cultivars and color break stages which appeared in the surface color, flesh color, firmness, soluble solids content (SSC), titratable acidity (TA) and vitamin C content. Strawberry fruit cv. Praratchatan 60 had the highest total soluble phenolics (TSP) and antioxidant activity (AA). Besides, AA from crude extracts of three strawberry cultivars notably correlated to their TSP (correlation coefficient (R) of 0.976). Furthermore, strawberry fruit harvested at 75% color break had higher SSC, vitamin C and anthocyanin content while being lower in firmness, TA, TSP and AA compared to those harvested at 25 and 50% color break.